Clinical management by telemonitoring for people with chronic disease in a Health Plan Operator - Aggio, Cristiane de Melo; Marcon, Sônia Silva; Haddad, Maria do Carmo Ferandes Lourenço (Seven Editora, 2023)
Objective: to report and analyze the implementation of clinical management by telemonitoring for people with chronic noncommunicable disease in a health insurance provider. Method: an evaluative, single-case study conducted in 2019, based on the models of description and reapplication of interventions and attention to chronic conditions. Clinical management by telemonitoring was the studied intervention. Results: adoption or maintenance of a healthy lifestyle was the goal of this intervention that assisted, on a monthly basis, up to 200 beneficiaries with non-communicable chronic disease, with low and medium clinical risk, from a medium-sized supplementary health operator located in the Center-south of Paraná-PR. Professionals from the multidisciplinary health team, trained in counseling for behavior change, carried out actions of health education and self-management supported by monthly, synchronous and previously scheduled telecontact, during 12 months. The phone calls were recorded and stored by the operator, and the activities and self-referred clinical data were recorded in electronic medical records. Conclusion: the clinical management by telemonitoring described was implemented in a favorable context, met the proposed objective and most elements of clinical management, innovated the care for beneficiaries with chronic noncommunicable diseases, and can be reproduced. DOI: https://doi.org/10.56238/colleinternhealthscienv1-053